Fostering Intercultural Education at Tertiary Level: A Case Study with Students of Humanities - Lemut Bajec, Melita (Revija za elementarno izobraževanje, 2024)
Intercultural education fosters respect, understanding, and solidarity, empowering individuals to become social agents in today’s culturally diverse world. The paper presents a 10-week case study involving 24 students enrolled in humanities disciplines. It explored students’ views on intercultural education, their progress in attitudes, knowledge, and skills related to intercultural competence, and effective instructional modes for intercultural education. Data collected using a questionnaire reveal that students value intercultural education for fostering understanding, appreciation of cultures, and intercultural dialogue. Effective instructional modes include active teaching methods. Challenges in overcoming well-established beliefs and a limited willingness to acquire new knowledge suggest that developing intercultural competence also depends on factors beyond education.
Keywords: instructional modes, intercultural competence, intercultural education, English, tertiary education.